2019
DOI: 10.1158/2159-8290.cd-19-0406
|View full text |Cite
|
Sign up to set email alerts
|

RAS Mutations Are Not Created Equal

Abstract: In this issue of Cancer Discovery , Poulin and colleagues apply structural, biochemical, and biological profi ling of two mutants of KRAS, one found most frequently in all cancers (G12D) and one found nearly exclusively in colorectal cancer (A146T). They provide compelling evidence that specifi c mutations will impart different structural and biochemical consequences on KRAS function and that the same KRAS mutation displays tissue-distinct signaling and biological consequences. Poulin et al., p. 738 (4). See r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…S3). These data and previous literature reports suggest structural, biochemical, and functional similarities among KRAS G12/13 and BRAF V600 mutations (Yao et al, 2015;Smith et al, 2013;Lu et al, 2016;Hunter et al, 2015;Hobbs et al, 2016;Hobbs and Der, 2019). For example, KRAS G12D, G12C, and G12V mutations exhibit similar crystal structure and hyperactivate RAS, leading to sustained activation of the RAF-MAP2K-MAPK1 signaling pathway (Li et al, 2018;Muñoz-Maldonado et al, 2019;Johnson et al, 2019;Ihle et al, 2012;Hobbs et al, 2016;Hunter et al, 2015;Smith et al, 2013;Lu et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…S3). These data and previous literature reports suggest structural, biochemical, and functional similarities among KRAS G12/13 and BRAF V600 mutations (Yao et al, 2015;Smith et al, 2013;Lu et al, 2016;Hunter et al, 2015;Hobbs et al, 2016;Hobbs and Der, 2019). For example, KRAS G12D, G12C, and G12V mutations exhibit similar crystal structure and hyperactivate RAS, leading to sustained activation of the RAF-MAP2K-MAPK1 signaling pathway (Li et al, 2018;Muñoz-Maldonado et al, 2019;Johnson et al, 2019;Ihle et al, 2012;Hobbs et al, 2016;Hunter et al, 2015;Smith et al, 2013;Lu et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, both KRAS and HRAS have higher activity toward NFκB activation in contrast to NRAS [37]. While being members of the most frequently mutated oncogene family in human cancer [38], RAS isoform mutants are clearly not equally prevalent in cancers [30]. KRAS mutations are overwhelmingly represented in cancers as whole compared to the other two isoforms.…”
Section: Ras Gtpases and Their Activationmentioning
confidence: 99%
“…The mammalian RAS GTPases consist of three gene isoforms, HRAS, NRAS, and KRAS, and four protein isoforms (splicing isoforms of KRAS give rise to KRAS4A and KRAS4B proteins). Whilst the isoforms share most of their sequence, substantial differences appear in the C-terminal so-called hypervariable regions and in post-translational modifications [28][29][30]. These differences in sequence and modification are considered to underlie the findings that RAS isoforms can function differentially in different biology and pathophysiology [31][32][33][34][35].…”
Section: Ras Gtpases and Their Activationmentioning
confidence: 99%
“…There is controversy among some experts who analyze the ovarian cancer prognosis associated with KRAS mutation. One researcher declared that KRAS mutation can occur at an early stage of ovarian cancer and had a good prognosis, on the other hand, there were researchers who reported that the KRAS mutation was associated with high recurrence rate and poor prognosis [5], [6]. The aim of this study is to prove that staging, grading, and KRAS exon 2 mutations will influence recurrence in epithelial ovarian cancer.…”
Section: Introductionmentioning
confidence: 90%